Analisis Internal Locus Of Control Terhadap Prokrastinasi Akademik Siswa - Nurani, Puspita; Muyana, Siti (JKI (Jurnal Konseling Indonesia), 2024)
The purpose of this study was to determine the effect of internal locus of control on procrastination of students at SMP Negeri 3 Blora. The population in this study was 254 students, while the sample in this study was 155 students who were determined through a simple random sampling technique with a lottery method. Content validity was carried out using the expert judgment method, while construct validity used product moment correlation and reliability with alpha cronbach. The results of the internal locus scale validity test were 34 items with a reliability result of 0.991, while the procrastination scale was 22 items with a reliability result of 0.922. The data analysis used simple linear regression. Based on the results of data analysis, the Anova Table obtained a calculated F value of 23.291 with a significance value of 0.000 (<0.05), meaning that the regression mode can be used to predict participation variables. Other data in the Summary Table shows an R value of 0.363 which is greater than the r table of 0.157, meaning that there is a relationship between internal locus of control and academic procrastination in students at SMP Negeri 3 Blora of 13.2%, the rest is influenced by other variables that are not explained in this study. The results of this study can be used as reference material in compiling guidance and counseling programs that are preventive or problem solving for students